Bygningar på museum - Vern - bruk - tilpassing? - Halvorsen, Kari-Bjørg Vold (Tidsskrift for kulturforskning, 2009)
This article discusses the reinterpretation of buildings preserved at museums. The issue arises out of an actual case: A building that was originally reconstructed at Norsk Folkemuseum in order to represent the early 19th century is about to be turned into a representation of the 1950s. This transformation means that the building has to be exposed to certain physical changes, which in turn raises several questions.